2016
DOI: 10.2174/1874210601610010438
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Enamel Thickness on Bleaching Efficacy: An In-Depth Color Analysis

Abstract: This study evaluated the influence of different enamel thicknesses and bleaching agents on treatment efficacy in-depth by spectrophotometry color analysis. Eighty bovine dental fragments were previously stained in black tea solution and randomly assigned into eight groups (n=10), 1.75mm dentin thickness and different enamel thicknesses as follows: 0.5mm, 1.0mm planned, 1.0mm unplanned (aprismatic enamel), and absence of enamel. The 10% carbamide peroxide (CP) and 35% hydrogen peroxide (HP) bleaching gels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 22 publications
(35 reference statements)
0
14
0
1
Order By: Relevance
“…Moreover, human and bovine teeth have been reported to exhibit similar behaviors during bleaching treatments [39]. Thus, the present study used bovine teeth as the testing substrates, in accordance with the previous studies [20, 28, 29, 40].…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, human and bovine teeth have been reported to exhibit similar behaviors during bleaching treatments [39]. Thus, the present study used bovine teeth as the testing substrates, in accordance with the previous studies [20, 28, 29, 40].…”
Section: Discussionmentioning
confidence: 59%
“…The bleaching agent applied to the surface of enamel must, in order to bring about the whitening effect, penetrate sufficiently through the enamel layer to the dentine to alter the color of the dentine immediately below the enamel, as bleaching through the enamel does not penetrate the entire depth of the dentine [ 16 ]. In addition, the data from a previous study demonstrated that the presence of at least 0.5 mm of enamel reduced the bleaching efficacy, and the presence of aprismatic enamel resulted in less color change in comparison to the group without aprismatic enamel [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the final results may be unpredictable [ 1 ]. In severely discolored teeth that are not responsive to routine vital bleaching, it may be necessary either to extend bleaching time [ 5 ] or to reduce the enamel surface for veneering without exposing underlying dentine to encourage penetration of bleaching agents into the stained dentine [ 6 , 7 ]. In attempting to treat severely discolored teeth by veneering, there is a considerable risk that the dark shade of the tooth tissue substrate will shine through relatively thin and translucent ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…Considering it, the use of bleaching systems composed only by hydrogen or carbamide peroxide on hypomineralized teeth by itself is not recommended. This is due because despite their ability to disintegrate pigmented molecules in tooth structure, the unstable free radicals generated during the oxide-reduction reaction of these agents are also able to decompose both organic and inorganic contents [9][10][11]. The consequences of this process may worsen the mechanical properties of hypomineralized affected teeth and yet highlight the appearance of MIH opacities [2].…”
Section: Discussionmentioning
confidence: 99%